2008
DOI: 10.2459/jcm.0b013e3282eee951
|View full text |Cite
|
Sign up to set email alerts
|

Patch size, shape and orientation affect geometrical outcomes of surgical anterior ventricular restoration

Abstract: The use of a small, narrow, obliquely oriented, oval patch may help to prevent adverse ventricular remodeling over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Raman et al associated the use of a stiff and relatively big patch in EVR as cause for some adverse long-term outcomes [94]. Patch size, shape and orientation may prove to be important in preventing adverse ventricular remodeling over time, as Cirillo et al have shown in a small group with an EVR technique using a small, obliquely oriented and oval-shaped patch [93]. Third, insufficient residual remote myocardium to survive the procedure and to translate the surgically induced morphological changes to functional improvement leads to LV failure.…”
Section: Fatal-failure Modes Of Lvrmentioning
confidence: 96%
“…Raman et al associated the use of a stiff and relatively big patch in EVR as cause for some adverse long-term outcomes [94]. Patch size, shape and orientation may prove to be important in preventing adverse ventricular remodeling over time, as Cirillo et al have shown in a small group with an EVR technique using a small, obliquely oriented and oval-shaped patch [93]. Third, insufficient residual remote myocardium to survive the procedure and to translate the surgically induced morphological changes to functional improvement leads to LV failure.…”
Section: Fatal-failure Modes Of Lvrmentioning
confidence: 96%
“…With use of an oval patch, EDV and ESV both improved significantly and had less re‐dilation at 6–12 months follow‐up 50 . It is hypothesized that these benefits may be due to the fact that an oval patch more accurately forms an ellipsoid shape when compared to the circular patch.…”
Section: Ventricular Function and Volumementioning
confidence: 99%
“…Even within one type of procedure, patch shape and size are also important considerations. In a study by Cirillo and colleagues, 50 the use of a circular patch improved end‐diastolic diameter (EDD), end‐systolic diameter (ESD), and EDV. However, at 1‐year follow‐up these measurements had returned to baseline.…”
Section: Ventricular Function and Volumementioning
confidence: 99%
See 1 more Smart Citation
“…10,11 However, late redilatation with mitral regurgitation has been reported. [12][13][14] Other methods such as the partial ventriculectomy of Batista et al, 15 the septal anterior ventricular exclusion 16 procedure, the apex restoring sutures of Buckberg et al, 17 and oval patch of Cirillo et al 12 Batista et al's 15 partial ventriculectomy, the septal anterior ventricular exclusion 16 procedure, Buckberg et al's 17 apex restoring sutures, and Cirillo et al's 12 oval patch and Keep flbers orientation with Strip patch reShaping (KISS) procedure 18 attempted to restore ventricular geometry. Although the amount of patients with true aneurysms is decreasing with modern reperfusion techniques, 19 information gathered on shape alteration might prove useful for patients with akinetic wall segments and diffuse dilatation.…”
mentioning
confidence: 99%